Evaluation criteria and a route selection system for transportating oversize and heavyweight cargoes - Petraška, Artūras; Palšaitis, Ramūnas (Transport, 2012)
Oversize and heavyweight cargoes are usually transported adopting a multimodal transport approach. Everything depends on the places where the cargoes are produced and used. The route for carrying oversize/heavy- weight cargo is usually evaluated and designed on individual basis. Thus, an important point is the development of an ‘instrument’ for an objective evaluation of the entire route for transporting oversize/heavyweight cargo (OHC).First Published Online: 19 Sep 2012